Маркетиннговий аналіз роздрібного ринку алкогольної продукції України - Мірошник, Марія Володимирівна; Лучна, Єлизавета Олексіївна; Стельмухова, Олена Олександрівна (НТУ "ХПІ", 2015)
Проведено аналіз роздрібного ринку алкогольної продукції України, визначено, що за даними ВООЗ Україна займає 61-е місце серед 100 країн: на душу дорослого населення за рік припадає понад 6 л абсолютного спирту. Деталізовано, що, одним із головних напрямкі в державної політики України є збалансована акцизна політика та унормування роздрібної торгівлі горілчаною продукцією заходи щодо вдосконалення контролю над виробництвом спирту етилового, горілки та лікеро-горілчаних виробів з метою як зменшення негативного соціального ефекту їх вживання, так й нівелювання існуючого тіньового ринку. Конкретизовані світові та провідні українські бренди горілчаної продукції, з метою вивчення переваг цільової аудиторії даної продукції проведено анкетування її споживачів.

An analysis of the retail market of alcoholic beverages in Ukraine, it is determined that according to the WHO Ukraine is the sixty-first place among 100 countries of the world, adult per capita in the year accounted for more than six liters of absolute alcohol. Detailed that in order to reduce the negative social impact of the use of alcoholic beverages, as well as minimizing the existing shadow market. One of the main directions of the state policy of Ukraine is balanced excise policy and regulation of retail beverages, activation of measures to improve control of the production of ethyl alcohol, vodka and distillery products. Fleshed out the world and the leading Ukrainian vodka brands. In order to study the preferences of the target audience of the product carried out a survey of its customers. It was stated that in 2014 the main negative factors for the decline in production of vodka production were: increase of excise duties on alcoholic beverages by 25% (h June 1, 2014 p. Increase in excise tax to 56.42 USD. / 1 liter of 100% alcohol to 70.53 USD. / 1 liter of 100% alcohol); the rising cost of raw materials; increasing the minimum retail price (from the beginning of 2015 the prices for vodka production increased on average by 8-10%).
Retail marketing analysis alcohol market of Ukraine
Keywords: роздрібні торгівельні підприємства; горілчана продукція; споживачі; українські бренди; Ukrainian brands; consumers